PENGARUH INPUT TERHADAP PRODUKSI USAHATANI LADA PUTIH (Muntok White Pepper) DI DESA KUNDI KECAMATAN SIMPANG TERITIP KABUPATEN BANGKA BARAT - Yudi Sapta Pranoto (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
The development of white pepper in Bangka Belitung Province is an interesting issue to be concerned, because of it has been well-known worldwide as Muntok White Pepper. This research based on the relationship among input, process, and output produced also high operating cost of white pepper farming. The focus of this research are (1) Calculating the amount of production cost, income, and the lowest output farmers’ price in Kundi Village, (2) Analyzing production inputs which allegedly influencing the amount of white pepper production in Kundi Village. The method used in this research was survey method and desk study and field study approach also data analyzing used Break Even Point and regression analysis used production function of Cobb Douglas, therefore the result of this research was (1) The amount of cost spent by the farmers in the first harvest season is Rp. 77.080.861, the income of white pepper farming in the first harvest season is Rp. 99.556.639. while BEP of price of white pepper is Rp.67.615 and BEP of Production of white pepper is Rp. 493 kilograms. (2) There are two variables influencing the amount of production of white pepper farming in Kundi Village, that is fertilizer (X1) and labor (X2).